2021
DOI: 10.3389/ijph.2021.1604396
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Violence Among Health Care Professionals in Public and Private Health Facilities in Bangladesh

Abstract: Objectives: The main objectives of this study were to examine the prevalence of workplace violence (WPV), its associated factors and explore the experiences of healthcare workers.Methods: A hospital-based cross-sectional study design used a nationally representative sample of 1,081 healthcare workers covering eight administrative divisions of Bangladesh. Logistic regression analysis was employed to estimate the adjusted effect of independent factors on WPV among healthcare workers.Results: Of the participants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 18 publications
(52 reference statements)
14
37
0
Order By: Relevance
“…This agrees with a study done in Saudi Arabia by Alshahrani and his colleagues, they addressed the importance of encouragement of authorities to facilitate reporting procedures of different violent incidents in order to help the implementation of strict penalties against perpetrators of violence towards healthcare professionals (Alshahrani et al, 2021). Other participants confirmed the importance of abundance of security personnel to help protect healthcare workers from chaos and violence, these suggestions agree with a study done in Bangladesh hoping to decrease workplace violence (Shahjalal et al, 2021). This also agrees with Ghosh (2018) who highlighted the importance of presence of nearby police stations and prevention of entrance of relatives of patients with any kinds of weapons or heavy tools, also transparency in addressing the fees of the administered services could help in overcoming patients' or relatives' anticipation and misunderstanding.…”
Section: Assaultssupporting
confidence: 85%
See 2 more Smart Citations
“…This agrees with a study done in Saudi Arabia by Alshahrani and his colleagues, they addressed the importance of encouragement of authorities to facilitate reporting procedures of different violent incidents in order to help the implementation of strict penalties against perpetrators of violence towards healthcare professionals (Alshahrani et al, 2021). Other participants confirmed the importance of abundance of security personnel to help protect healthcare workers from chaos and violence, these suggestions agree with a study done in Bangladesh hoping to decrease workplace violence (Shahjalal et al, 2021). This also agrees with Ghosh (2018) who highlighted the importance of presence of nearby police stations and prevention of entrance of relatives of patients with any kinds of weapons or heavy tools, also transparency in addressing the fees of the administered services could help in overcoming patients' or relatives' anticipation and misunderstanding.…”
Section: Assaultssupporting
confidence: 85%
“…The fore mentioned study highlighted the importance of increasing awareness about the impact of violence on health sector which was a solution also proposed by the participants in the current study (Shahjalal et al, 2021).…”
Section: Assaultsmentioning
confidence: 75%
See 1 more Smart Citation
“…A positive culture should be created to combat WPV. A harmonious nurse–patient relationship, respect, tolerance, gender sensitivity, equality, collaboration, and care should be practiced, and no form of WPV should be tolerated (Shahjalal et al., 2021 ). Staff and patient ratios should be improved by recruiting new staff that will minimize time pressure on health workers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it is not a new issue in Bangladesh that HCWs are subjected to WPB and WPV. A recent study carried out in Bangladesh reported that a high proportion of healthcare professionals (43%) experienced some form of WPV [ 24 ]. Several studies in many countries found a relationship between WPV and burnout among nurses [ 25 27 ].…”
Section: Introductionmentioning
confidence: 99%